A Single-Stage Low-Power Double-Balanced Mixer Merged with LNA and VCO - Nam-Jin Oh (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper proposes three types of single stage low-power RF front-end, called double-balanced LMVs, by merging LNA, mixer, and voltage-controlled oscillator (VCO) exploiting a series LC (SLC) network. The low intermediate frequency (IF) or baseband signal can be directly sensed at the drain nodes of the VCO switching transistors by adding a simple resistor-capacitor (RC) low-pass filter (LPF). By adopting a double-balanced mixer topology, the strong leakage of the local oscillator (LO) at the IF output is effectively suppressed. Using a 65 nm CMOS technology, the proposed double-balanced LMVs (DB-LMVs) are designed. Oscillating at around 2.4 GHz ISM band, the phase noise of the proposed three DB-LMVs is −111 dBc/Hz at 1 MHz offset frequency. The simulated voltage conversion gain is larger than 36 dB and the double-side band (DSB) noise figure (NF) is less than 7.7 dB. The DB-LMVs consume only 0.2 mW dc power from 1-V supply voltage.